Неэффективное землепользование и пути его преодоления - Сааджан, И.А. (Економічні інновації, 2012)
В статье исследуются современные тенденции проблемы землепользования и сроков превышения освоения как одной из форм его проявления. Рассмотрены законодательно-нормативные аспекты и разработаны рекомендации по их устранению. The article investigates the current trends in violations of land in Ukraine, as a cause of protracted waste of resource management, legal and regulatory aspects of the prospects for protracted combat in Ukraine and Russia. Proposals to improve the efficiency of land use.